Community-acquired pneumonia in the post 13-valent pneumococcal conjugate vaccine era. Issue 6 (December 2016) - Shaughnessy, Erin E.; Stalets, Erika L.; Shah, Samir S.
Abstract : Purpose of review: This review covers the outpatient management of pediatric community-acquired pneumonia (CAP), discussing the changing microbiology of CAP since the introduction of the 13-valent pneumococcal conjugate vaccine in 2010, and providing an overview of national guideline recommendations for diagnostic evaluation and treatment. Recent findings: Rates of invasive pneumococcal disease and pneumococcal antibiotic resistance have plummeted since widespread 13-valent pneumococcal conjugate vaccine immunization. Viruses remain the most common cause of CAP in young children; children over age 5 years have increased rates of Mycoplasma pneumoniae . A recent national guideline offers recommendations for office-based diagnostic evaluation and treatment of pediatric CAP. Summary: This review offers a discussion of the above findings with practical recommendations for the office-based practitioner in the evaluation and treatment of an infant (>3 months) or child with suspected CAP.